Kenya : Request for a Three-Year Arrangement under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2004)
Kenya showed poor implementation of policies and weak economic performance under the Poverty Reduction and Growth Facility (PRGF) arrangement. The government formulated a new Economic Recovery Strategy for Wealth and Employment Creation (ERSWEC) aimed to address major macroeconomic vulnerabilities. Executive Directors emphasized the need for domestic debt reduction, the restructuring of spending, and a sustained implementation of the reform agenda. They suggested that bold reforms will be essential to encourage private investment and to mobilize adequate donor support for the reforms.